A Feasibility study on KERSH Corn Chips - Lee, Maridel A.; Loyola, Girlee A.; Ong, Aleth Arther M.; Rosales, Ryan C. (Diliman, Quezon City College of Engineering, 1998)
This study focuses on the feasibility of manufacturing a new corn chip made from squash and corn flour, thus introducing a nutritious snack food in the market. The utilization of squash yields 504 meq Beta-carotene for every 100 grams and it can even supplement 26% of a pre-schooler's daily requirement for Vitamin A. The product shall be called KERSH CORN CHIPS, its name derived from the words kernel and squash. The target market were consumers from the NCR, aged 5 to 24 years old. The supply and demand analysis revealed that there exists an unsatisfied demand for snack foods amounting to an average of 22 million kilograms per year. It is therefore suitable for the company to venture as a medium-scale manufacturer with an initial production of 1,140,000 kilograms of KERSH on its first year, capturing a 3.95% market share in metro Manila. The product shall compete in terms of nutritional value and low price offered at PhP 0.12 per gram. It shall be marketed in 15-45 and 90 gram packs and offered in 3 flavors namely cheese, barbecue and sour cream & onion. An aggressive marketing strategy with a budget of PhP 1,100,454.00 shall be employed for the first year. The technical study showed that the raw materials and other indirect materials for the production of KERSH can be obtained from the local market all-year round. The available technology makes it possible to purchase from local manufacturers and distributors the equipment and machinery required. Fifty seven (57) production workers paid with hourly wages and 42 regular workers and administrative personnel with fixed salaries shall be employed to meet the demand for production. Six days per week and two shifts per day shall be allotted for production. An industrial lot covering an area of 2,300 square meters, located in Santo Cristo, San Jose del Monte, Bulacan shall be used as plant site. The said location is sufficient to cover the required land area of 1,349 square meters. The cost of the project totals to PhP 81,775,205.00. In order to put up the said amount of capital, KERSH FOOD CORPORATION shall be established and a 75.25 equity to debt ratio shall be employed by issuing stocks and acquiring loan from Far East Bank and Trust Co. The financial analysis indicated that it is financially feasible to venture into the project with a payback period of 3 years and 5 months. The internal rate of return is 35% which is greater than the set MARR of 20%. The organization and management study and the social profitability study also suggests that the formation and management required can be established and benefits can be generated from the project. The income of local raw materials manufacturers shall be increased as well as the national and local government's income which can be accounted to the taxes to be paid by the corporation. Bulacan's unemployment rate shall also decrease by 0.0796% and nutritious snack food shall be marketed to the public at an affordable price. The above results therefore suggests that it is a favorable idea to venture into the production of KERSH CORN CHIPS.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: KERSH Food Corporation; Corn products industry; Corn chips; Participatory monitoring and evaluation (Project management)